2018
DOI: 10.22266/ijies2018.0430.30
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Ensured Semantic Movie Recommendation by Applying Linked Open Data

Abstract: Abstract:The recommender system becomes a significant research area due to the popularity of the social web. Traditional semantic recommender systems deliver poor performance when balancing the recommendation accuracy and diversity. Also, the rank-based recommendation methods lack to obtain the coverage of the entire preferences of the user in the top-N recommendation list. Thus, this paper presents the Diversity-Ensured Semantic-aware Item REcommendation (DESIRE) that deals with the consistent and reliable kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…With the help of open linked data, it is feasible to provide such services to users (Corsar et al, 2017). The DESIRE recommender system is designed to improve the performance of movie recommendations by keeping both the accuracy and diversity at an optimal level (Srinivasan & Mani, 2018). From the above analysis, it is concluded that none of the existing methods fully utilizes the available semantic information in LOD for cold start and data sparsity problem.…”
Section: Lod Enabled Rsmentioning
confidence: 99%
“…With the help of open linked data, it is feasible to provide such services to users (Corsar et al, 2017). The DESIRE recommender system is designed to improve the performance of movie recommendations by keeping both the accuracy and diversity at an optimal level (Srinivasan & Mani, 2018). From the above analysis, it is concluded that none of the existing methods fully utilizes the available semantic information in LOD for cold start and data sparsity problem.…”
Section: Lod Enabled Rsmentioning
confidence: 99%
“…When considering the differences in user preferences for different directories, researchers proposed a personalized diverse algorithm based on the greedy re‐ranking strategy to jointly optimize relevance and diversity 7 . The improvement of diversity in re‐ranking is a popular research direction 8‐11 …”
Section: Related Workmentioning
confidence: 99%